Adaptations to family-based treatment for Medicaid-insured adolescents with anorexia nervosa - Borges, Renee; Crest, Peyton; Landsverk, John; Accurso, Erin C. (Frontiers in Psychology, 2024)
Background: Family-based treatment (FBT) is the leading intervention for adolescents with anorexia nervosa (AN), however it is under researched in socioeconomically disadvantaged and racially diverse youth.Methods: Semi-structured interviews were completed with ten FBT clinicians who practice in publicly-funded settings. Interview questions were focused on implementation challenges, overall acceptability and appropriateness of FBT, and naturally-occurring treatment adaptations.Results: Content analysis revealed common themes relating to the implementation of FBT in publicly-funded, community-based settings: acceptability and appropriateness, complexity and learnability, perceived core components of FBT, cultural adaptations, socioeconomic factors, logistical considerations, organizational and systemic barriers, training acceptability, participant's self-efficacy, and telehealth accommodations.The discussed themes offer insights into the implementation of FBT for settings with limited resources, aligning with prior research on clinical adaptations for multicultural patients. Recognizing these themes can guide clinical adjustments and refine the adapted treatment model in real-world settings for patients facing systemic barriers.